ℒ1 adaptive output feedback control of small unmanned aerial vehicles - Souanef, Toufik (World Scientific Publishing, 2022)
An approach for output feedback ℒ1 adaptive control of small Unmanned Aerial Vehicles (UAVs) is presented in this paper. The design is based on a state observer instead of the state predictor. The main advantage is that a full state measurement can be avoided, and the design and implementation of the controller are simplified. Furthermore, since the state space description is maintained, the system dynamics including uncertainties can be specified with physical insight, which simplifies practical applications. The adaptation law borrows insights from the sliding mode control to estimate the unknown bounds of external disturbances. Flight test results for the control of a small UAV show the robustness of the ℒ1 adaptive controller to large uncertainties and disturbances.
Keywords: ℒ1 Adaptive Control; Unmanned Aerial Vehicles; Fault-tolerant Control; Output feedback Control